Disulfide‐Bridged Organosilica Frameworks: Designed, Synthesis, Redox‐Triggered Biodegradation, and Nanobiomedical Applications. (25th April 2018) - Du, Xin; Kleitz, Freddy; Li, Xiaoyu; Huang, Hongwei; Zhang, Xueji; Qiao, Shi‐Zhang
Abstract: Over the past few years, silica‐based nanotheranostics have demonstrated their great potential for nano/biomedical applications. However, the uncontrollable and difficult degradability of their pure silica framework and long‐time in vivo retention still cause severe and unpredictable toxicity risks. Therefore, it is highly desirable to design and synthesize materials with safer framework structures and compositions. To this aim, the introduction of disulfide bonds into the silica framework can not only maintain high stability in physiological conditions, but also achieve a stimuli‐responsive biodegradation triggered by intracellular reducing microenvironment in living cells, especially in cancer cells. Once nanotheranostics with disulfide (i.e., thioether)‐bridged silsesquioxane framework are taken up by tumor cells via passive or active targeting, the disulfide bonds in the hybrid silica matrix can be cleaved by a high concentration of intracellular glutathione, enabling redox‐triggered biodegradation of the nanosystems for both concomitant release of the loaded therapeutic cargo and in vivo clearance. It is envisioned that such hybrid materials comprised of disulfide‐bridged silsesquioxane frameworks can become promising responsive and biodegradable nanotheranostics. This review summarizes the recent advances in the synthesis of hybrid organosilicas with disulfide‐bridged silsesquioxane frameworks, and discuss their redox‐triggered biodegradation behaviors combined with their biocompatibility and nanobiomedical applications. Abstract : An overview of the designed synthesis of nanomaterials consisting of disulfide‐bridged organosilica frameworks, their intracellular redox‐triggered biodegradation behaviors, and emerging nanobiomedical applications is provided in this feature article.